Male-only care and cuckoldry in black coucals: does parenting hamper sex life?. Issue 1900 (10th April 2019) - Safari, Ignas; Goymann, Wolfgang; Kokko, Hanna
Abstract : Providing parental care often reduces additional mating opportunities. Paternal care becomes easier to understand if trade-offs between mating and caring remain mild. The black coucal Centropus grillii combines male-only parental care with 50% of all broods containing young sired by another male. To understand how much caring for offspring reduces a male's chance to sire additional young in other males' nests, we matched the production of extra-pair young in each nest with the periods during which potential extra-pair sires were either caring for offspring themselves or when they had no own offspring to care for. We found that males which cared for a clutch were not fully excluded from the pool of competitors for siring young in other males' nests. Instead, the relative siring success showed a temporary dip. Males were approximately 17% less likely to sire young in other males' nests while they were incubating, about 48% less likely to do so while feeding nestlings, followed by 26% when feeding fledglings, compared to the success of males that currently did not care for offspring. These results suggest that real-life care situations by males may involve trade-off structures that differ from, and are less strict than those frequently employed in theoretical considerations of operational sex ratios, sex roles and parenting decisions.